A Longitudinal Study on the Changes in Mental Health of Healthcare Workers during the COVID-19 Pandemic. Issue 1 (2nd January 2022) - López Steinmetz, Lorena Cecilia; Herrera, Carla Romina; Fong, Shao Bing; Godoy, Juan Carlos
Abstract : Objective : This study examines Argentinean health care workers in order to 1) test self-perceived job performance levels and the presence of psychological symptoms compatible with common mental disorders, and 2) examine within-person changes in general discomfort and psychological distress, adjusting for demographic factors, region, and health-related factors during two time points of the COVID-19 pandemic. Method : This longitudinal study comprised 305 healthcare workers who completed a survey at two time points approximately 4 months apart. We used the General Health Questionnaire and the Kessler Psychological Distress Scale to measure mental health outcomes. To address the first aim we calculated differences (Student's t test for paired samples) and correlations (Pearson's r coefficient). To address the second aim we used fixed effects model by means of a multilevel approach, a linear model that considers dependency in the data. Results : Self-perceived job performance deteriorated across time. From the first measurement to the four-month follow-up, more health care workers presented common mental disorders (40% vs 45.57%), depression, and/or anxiety (52.46% vs 62.62%). A meaningful worsening of mental health was observed in healthcare workers who expressed concern about being infected with COVID-19, whether asymptomatic (greater general discomfort and psychological distress) or symptomatic (greater general discomfort). Likewise, there were significant interactions between a history of mental disorder and concern about COVID-19 infection. Conclusions : Among healthcare workers, the uncertainty about the COVID-19 infection may have larger negative mental health impacts than actually being infected.